Study Of WSNs: Its Application and Types - andey, Prachi P (International Journal of Scientific Research and Management (IJSRM), 2015)
Recent years have witnessed the power of WSNs as a most secure network communication medium. Among that a widevarieties of sensor networks and their variants have found their application and uses. The development of wireless sensornetworks was motivated by a number of military applications such as battlefield surveillance along with a lot more areasof life. The design of a WSN depends significantly on the application, and it must consider factors such as theenvironment, the application’s design objectives, cost, hardware, and system constraints. There are many Size and costconstraints on sensor nodes that result in constraints on resources such as high speed. energy, good memory, andcommunications bandwidth. This has been enabled by the availability, particularly in recent years, of sensors that areintelligent and cheaper. These sensors are made with wireless interfaces through which they can communicate with oneanother to form a network. The goal of our survey is to present a comprehensive review of lot of works done on WirelessSensor Networks.